Caracterización de esquemas terapéuticos en la Unidad de Trasplante de Médula Ósea del Hospital Nacional Edgardo Rebagliati Martins, enero-diciembre 2016 - Diaz Flores, Luis Enrique (2018)
The present research work is a descriptive study, whose objective was to characterize the therapeutic schemes of the Bone Marrow Transplant Unit of the Edgardo Rebagliati Martins National Hospital, January-December 2016. The information collected from the recipes, provided information on the main diseases, therapeutic schemes, cost of pharmacological therapy and drug interactions according to severity. According to the study, the main diseases undergoing allogeneic transplantation were obtained: Acute B Lymphoblastic Leukemia, Acute Myeloid Leukemia, Severe Aplastic Anemia, Non-Hodgkin's Lymphoma, Non-Severe Aplastic Anemia, Hypoplasia / Dysplasia, and Myelodysplastic Syndrome / Hemoglubinuria Nocturnal Paroxysm, with a total of 6 schemes distributed in 25 patients according to their disease: Busulfan - Cyclophosphamide (Bu-Cy), Radiation - Cyclophosphamide - Cyclosporine (TBI-CTX), Radiation-Cyclophosphamide - Mycophenolate mofetil (TBI-CTXHaplo), Fludarabine - Busulfan (Flu-Bu), Antimiocytic Globulin - Cyclophosphamide (GAT-Cy), Cyclophosphamide - Fludarabine - Radiation (Cy-Flu-TBI) (28%, 12%, 28%, 8%: 20% and 4% respectively) and autologous: Multiple Myeloma (MM), Follicular NHL, NHL, Primary Gastric NHL, MM of light chains and Neuroblastoma, with a total of 4 schemes distributed in 16 patients according to their disease: Melphalan, Melfalan-Busulfan, Rituximab-Carmustin a-Etoposide-Cytarabine-Cyclophosphamide (R-BEAC), Rituximab-Carmustine-Etoposide-Cytarabine-Melphalan (R-BEAM) (56.3%; 6.3%; 18.8% and 18.8% respectively). The drug interactions of greater, moderate and minor (9.3%, 77.2% and 12.7% respectively). The therapeutic schemes used were leukemias, lymphomas, myelomas, among others. Whose drug interactions are of moderate severity